"Self‐Lockable" Liquid Crystalline Diels–Alder Dynamic Network Actuators with Room Temperature Programmability and Solution Reprocessability. Issue 12 (18th February 2020) - Jiang, Zhi‐Chao; Xiao, Yao‐Yu; Yin, Lu; Han, Li; Zhao, Yue
Abstract: Novel main‐chain liquid crystalline Diels—Alder dynamic networks (LCDANs) were prepared that exhibit unprecedented ease for actuator programming and reprocessing compared to existing liquid crystalline network (LCN) systems. Following cooling from 125 °C, LCDANs are deformed with aligned mesogens self‐locked at room temperature by slowly formed Diels–Alder (DA) bonds, which allows for the formation of solid 3D actuators capable of reversible shape change, and strip walker and wheel‐capable light‐driven locomotion upon either thermally or optically induced order–disorder phase transition. Any actuator can readily be erased at 125 °C and reprogrammed into a new one under ambient conditions. Moreover, LCDANs can be processed directly from melt (for example, fiber drawing) and from solution (for example, casting tubular actuators), which cannot be achieved with LCNs using exchangeable covalent bonds. The combined attributes of LCDANs offer significant progress toward developing easily programmable/processable LCN actuators. Abstract : Liquid crystalline dynamic networks can be shaped into 3D objects at room temperature while being stabilized by slowly formed Diels–Alder‐bonded (DA) cross‐links. The actuators demonstrate thermally or optically induced reversible shape change for the purpose of performing mechanical work or locomotion.